Ketut Muhammad: Sistem Penamaan Diri Muslim Pegayaman di Bali - Aliffiati Aliffiati; Ida Bagus Oka Wedasantara; Gede Budarsa (Umbara, 2023)
Name is the basic identity for a person. The Pegayaman muslims community has a distinctive naming pattern that has integrated Balinese Hindu culture. This paper aims to explore the Pegayaman muslim self-name system with the subject of the system of determining the name, naming based on birth order and naming with Islamic nuances. This study employed qualitative methods. The data were collected by using interview and observation. The results showed that the system of naming children in the Pegayaman community based on birth order follows the Hindu Bali cultural naming system, namely Wayan, Nengah, Nyoman and Ketut. A naming system based on gender was also found, namely Siti for the female group and Muhammad for the male group. This name is then combined with names with Islamic nuances taken from Islamic figures, names of the Prophet, Islamic teachings, national figures and so on. This finding indicates that the naming system in the Pegayaman Muslims community has high complexity. This complexity is inseparable from the integration of Balinese culture in their lives. This phenomenon indicates that the Pegayaman community has a high tolerance, moderate and inclusive attitude.